Workers coping in organizations during trying times: a dynamic and cyclical health action process and evidence-based approach. - Ferreira, A.I.; Antunes, A.; N. Pereira; Costa Ferreira, P.A. N. (83rd Annual Meeting of the Academy of Management, 2023)
This study proposes to examine which strategies organizations can focus on to effectively and sustainably grasp their employee’s potential during a pandemic and how strategic planning can be adapted to warrant the importance of human resource sustainability, using a dynamic and cyclical health action process approach. It also proposes to investigate what the longitudinal relationship and potential impact of the challenges presented by the pandemic are on employees and organizations with respect to the enactment of DGS guidelines, work engagement, leaders’ moral (dis)engagement, and employees’ decision to remain in their company in the context of the pandemic caused by COVID-19. To study multidimensional measures, a mixed study was conducted with qualitative and quantitative data. Interviews were conducted and questionnaires were applied at two different times, corresponding to two general confinement phases and were analyzed using thematic analysis and Structural Equation Modelling, respectively. Results showed what motivated organizations and their employees to adopt new prevention and containment measures. Based on the Social Cognitive Theory and Social Exchange Theory, different repercussions (negative and positive) of the HAPA constructs on certain organizational outcomes were confirmed. Specifically, the effects on the Leader’s Moral Disengagement, on Enactment of Sanitation Guidelines provided by the Directorate-General for Health (DGS), on Work Engagement, and on employees’ Decision to remain in the company, were confirmed. The study presents theoretical, practical contributions and suggestions for future investigations.